2023
DOI: 10.1002/wer.10872
|View full text |Cite
|
Sign up to set email alerts
|

Systematic studies on the effect of structural modification of orange peel for remediation of phenol contaminated water

Abstract: In the present study, orange peel biochar has been utilized as the adsorbent for the removal of phenol from contaminated water. The biochar was prepared by thermal activation process at three different temperature 300, 500 and 700°C and are defined as B300, B500, and B700 respectively. The synthesized biochar has been characterized using scanning electron microscopy (SEM), X‐ray diffraction (XRD), Fourier transformation infrared spectroscopy (FTIR), RAMAN spectroscopy, X‐ray photoelectron spectroscopy (XPS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The surface area values found in this work are lower than most of the activated carbons. However, these values are in the order of other carbon adsorbents obtained from different natural residues reported in the literature: da Silva et al [5] found surface area values in the range 166-400 m 2 /g for carbons obtained from citrus fruit residues, Verma et al [11] found values of 207 m 2 /g and 37 m 2 /g for carbon adsorbents derived from waste biomass of citrus limetta (peel and pulp), Kumar et al [6] found 67.5 m 2 /g for biochars obtained from orange peel residues, Ahmadian et al [2] found 195 m 2 /g for biochars obtained from lemon peel and Aboli et al [50] found 7.2 m 2 /g for carbons prepared from citrus limetta leaves. It should be remarked that the impregnation step, the mixture of the carbonaceous precursor with FeCl 3 , is usually performed by two different methods: in an aqueous solution or by physical mixing between the carbon precursor and the iron chloride activating agent.…”
Section: Adsorbents Characterizationmentioning
confidence: 87%
See 1 more Smart Citation
“…The surface area values found in this work are lower than most of the activated carbons. However, these values are in the order of other carbon adsorbents obtained from different natural residues reported in the literature: da Silva et al [5] found surface area values in the range 166-400 m 2 /g for carbons obtained from citrus fruit residues, Verma et al [11] found values of 207 m 2 /g and 37 m 2 /g for carbon adsorbents derived from waste biomass of citrus limetta (peel and pulp), Kumar et al [6] found 67.5 m 2 /g for biochars obtained from orange peel residues, Ahmadian et al [2] found 195 m 2 /g for biochars obtained from lemon peel and Aboli et al [50] found 7.2 m 2 /g for carbons prepared from citrus limetta leaves. It should be remarked that the impregnation step, the mixture of the carbonaceous precursor with FeCl 3 , is usually performed by two different methods: in an aqueous solution or by physical mixing between the carbon precursor and the iron chloride activating agent.…”
Section: Adsorbents Characterizationmentioning
confidence: 87%
“…Nowadays, agricultural and food processing activities generate huge amounts of solid wastes, which are commonly eliminated by burning, bringing on different ecological and environmental problems [1]. Agricultural waste is cheap, and it includes husks, peels, and shells of different crops such as rice, sunflower, palm, citric, or different kinds of nuts [2][3][4][5][6]. Most of this waste contains such compounds as starch and lignocellulosic biomass including cellulose, hemicellulose, and lignin [7,8], all of them with a high content of carbon, and were easily transformed into activated carbons or biochar under pyrolysis processes [9,10].…”
Section: Introductionmentioning
confidence: 99%